Physiological responses and characteristics of table tennis matches determined in official tournaments - Zagatto, A. M.; Morel, E. A.; Gobatto, C. A. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to verify the physiological responses and the match characteristics of table tennis and also to compare these responses in 2 different performance-level athletes from official tournaments. Twenty male table tennis players (12 regional experience-RP and 8 national and international experience-NP) were participants in the study. Blood lactate concentration ([LAC]) and heart rate (HR) were measured as physiological parameters in 21 official table tennis matches, and other 12 matches had recorded the duration of rally (DR), rest time, effort and rest ratio (E:R), total playing time (TPT), effective playing time (EPT), and frequency of shots by video analyses. The [LAC] verified in all matches was 1.8 mmol/L (+/-0.8), whereas the [LAC] peak was 2.2 mmol/L-1 (+/-0.8). There were no significant differences between the 2 groups (p > 0.05) in both parameters. The HR was 164 b/min (+/-14), corresponding to 81.2% (+/-7.4) of the predicted maximum HR. As characteristics of the matches, the DR corresponded to 3.4 seconds (+/-1.7), rest time to 8.1 seconds (+/-5.1), E:R to 0.4 (+/-0.2), TPT to 970.5 seconds (+/-336.1), EPT to 44.3% (+/-23.7), and frequency of shots to 35.3 balls/min (+/-7.7). Among groups, the rest time was lower in RP than in NP. Consistently, the E:R and EPT were higher in RP than in NP (p < 0.05). The results suggest that table tennis matches present the aerobic system as a principal output energy, the phosphagenic system being the most important during efforts. The information pertaining to the physiological profile and the characteristics of table tennis should be used by coaches planning physical training and specific exercise prescriptions aiming at achieving maximal sport performance.